MicroRNA‐155 is a biomarker of T‐cell activation and immune dysfunction in HIV‐1‐infected patients. Issue 5 (16th December 2016) - Jin, C; Cheng, L; Höxtermann, S; Xie, T; Lu, X; Wu, H; Skaletz‐Rorowski, A; Brockmeyer, NH; Wu, N
Abstract : Objectives: MicroRNA‐155 (miR‐155) regulates T‐cell differentiation and activation. It has also been associated with HIV infection. However, it remains unclear whether miR‐155 is related to the T‐cell response in HIV‐infected individuals (e.g. T‐cell activation and exhaustion). Methods: We performed a cross‐sectional study involving 121 HIV‐1‐infected patients on highly active antiretroviral therapy (HAART) and 43 HAART‐naïve patients. MiR‐155 levels in the peripheral blood were determined by quantitative reverse transcription–polymerase chain reaction (PCR). T‐cell immune activation, exhaustion, and homeostasis were measured by determining the expression of CD38, programmed death 1 (PD‐1) and CD127 via flow cytometry. Results: The levels of miR‐155 in total peripheral blood mononuclear cells, CD4 T cells and CD8 T cells from HIV‐1‐infected patients were increased ( P < 0.01). Nonresponders and HAART‐naïve patients also exhibited a higher percentage of CD8 + CD38 + T cells and a lower percentage of CD4 + CD127 + and CD8 + CD127 + T cells ( P < 0.05). We also found higher levels of PD‐1 expression on the CD4 + and CD8 + T cells of HIV‐1‐infected patients ( P < 0.05). Conclusions: Our findings suggest that miR‐155 levels in the peripheral blood of HIV‐1‐infected patients are increased and associated with T‐cell activation. Therefore, miR‐155 is a potential biomarker of the immune response following HIV‐1 infection.